Exploring the Impact of Digital Marketing in Increasing Brand Awareness of Gudang Garam Cigarettes (A Case Study of Cigarette Consumers in Dayeuhkolot) - Ibnu, Ghazi M. Naufal; Arry, Widodo (Ekonika : Jurnal Ekonomi Universitas Kadiri, 2025)
This study was conducted to determine the effect of Digital Marketing on Brand Awareness, based on the decline in Brand Value experienced by one of Indonesia’s leading cigarette manufacturers, Gudang Garam. The purpose of this research was to examine and analyze the implementation of Digital Marketing, the level of Brand Awareness, and the influence of Digital Marketing on brand awareness within the company. This study employed a quantitative, descriptive, and causal approach. The sampling technique employed was purposive sampling, a type of non-probability sampling, with a total of 100 respondents. Data were analyzed descriptively, and hypotheses were tested using simple linear regression analysis. The findings show that Digital Marketing has a significant effect on Brand Awareness. The coefficient of determination indicates that Digital Marketing explains 16.4% of Brand Awareness, while the remaining 83.6% is influenced by other factors not examined in this study, such as promotion or product experience. Results also show that Gudang Garam’s Digital Marketing is categorized as “not good,” while Brand Awareness is considered “good enough.” However, some aspects require improvement, particularly the low consumer motivation to try the product after watching its YouTube ads, which highlights the need for clearer messaging, stronger emotional appeal, and more strategic positioning in future digital efforts.